TEACHING ENGLISH FOR SPECIFIC PURPOSES: DEVELOPING METHODOLOGICAL FRAMEWORKS FOR ECONOMICS, TOURISM, AND COMPUTER ENGINEERING STUDENTS - Akhmadjonov , Avazbek (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
The globalized professional landscape has rendered English for Specific Purposes (ESP) an indispensable component of higher education, particularly in fields with intense international collaboration such as Economics, Tourism, and Computer Engineering. However, a significant pedagogical challenge lies in effectively tailoring instruction to address the distinct discursive practices and evolving needs of students across different academic years. This thesis argues that a successful ESP curriculum must move beyond a one-size-fits-all model and adopt a tiered, genre-based approach that progressively builds complexity from foundational to advanced communicative competence. Through a mixed-methods analysis—incorporating discourse analysis of authentic professional texts, student needs surveys, and a review of pedagogical frameworks—this study proposes a structured three-year model. For first-year students, the focus is on core terminology and fundamental genre mastery. Second-year instruction escalates to complex sentence structures and intermediate genres like economic reports and software development blogs. The final year emphasizes sophisticated discourse analysis, negotiation skills, and the production of original, professional-grade texts such as project proposals and technical white papers. The findings demonstrate that such a differentiated, sequential framework significantly enhances student motivation, linguistic accuracy, and pragmatic competence, ultimately bridging the gap between academic language learning and real-world professional communication.